2010
DOI: 10.1111/j.1574-695x.2010.00753.x
|View full text |Cite
|
Sign up to set email alerts
|

The calcineurin inhibitor RCAN1 is involved in cultured macrophage and in vivo immune response

Abstract: Studies on the role of regulator of calcineurin 1 (RCAN1) in immunity are limited, but have demonstrated an involvement in T-lymphocyte function. Here, we expand these studies to macrophages and in vivo infection. The treatment of RAW and primary mouse macrophages with lipopolysaccharide from Escherichia coli strongly induced RCAN1 isoform 4 (RCAN1-4), but not isoform 1. RCAN1-4 induction involved calcium, calcineurin, and reactive oxygen species. Subsequent analysis with whole bacteria including gram-negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…The data of the present study show that the Gram-negative putative periodontal pathogen P. gingivalis increases the expression of rcan1 as much as VEGF, which is one of the main regulators of rcan1 . This and other results indicate that TLR4 receptors may be involved in the regulation of rcan1 [ 34 ]. Furthermore, the observed phenomenon might display a short-term mechanism that limits the early immune response towards P. gingivalis , thus avoiding any collateral damage due to an overreacting inflammation.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The data of the present study show that the Gram-negative putative periodontal pathogen P. gingivalis increases the expression of rcan1 as much as VEGF, which is one of the main regulators of rcan1 . This and other results indicate that TLR4 receptors may be involved in the regulation of rcan1 [ 34 ]. Furthermore, the observed phenomenon might display a short-term mechanism that limits the early immune response towards P. gingivalis , thus avoiding any collateral damage due to an overreacting inflammation.…”
Section: Discussionsupporting
confidence: 57%
“…Rcan1 expression is mediated through numerous stimuli including calcium-elevating agents and cell receptor agonists like VEGF and thrombin [ 33 ]. Moreover, expression of rcan1 can be induced by Gram-positive and Gram-negative bacteria [ 34 ]. The data of the present study show that the Gram-negative putative periodontal pathogen P. gingivalis increases the expression of rcan1 as much as VEGF, which is one of the main regulators of rcan1 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has focused on the role of RCAN1 in the production of various inflammatory cytokines in response to immunological stimuli (45). However, the biological implications of RCAN1 during infection remain poorly understood.…”
mentioning
confidence: 99%
“…Induction of inflammatory mediators was also reduced and there was a marked reduction in leukocyte infiltrate in the heart, liver and lungs [152]. Another study found that following infection with the bacteria Fransicella tularensis, induction of proinflammatory cytokines including MCP1, IL6, IFNγ, and TNFα was significantly higher in Rcan1-deficient spleen and lung [153]. All this suggests that over-expression of RCAN1 is protective.…”
Section: Rcan1 In Innate Immunitymentioning
confidence: 96%